Analisis Nilai pH Sebelum dan Setelah Penggunaan Kapur Dolomit [(CaMG (CO3)] Terhadap Kegiatan Minapadi di Desa Sungai Dua - Rani Ria Rizki; Ikromatun Nafsiyah; Diki Afreza; Wijianto (Clarias : Jurnal Perikanan Air Tawar, 2021)
South Sumatra has a fairly large swamp area and has the potential for rice and fish cultivation activities. Swampland has a fairly low or acidic pH content so that before using it fairly large for fish and rice cultivation processes, it is necessary to treat the land, one of which is liming so that it can increase the pH value. The main purpose of this study was to determine the optimal pH value of water after liming for Minapadi in tidal swamp areas. The benefit is to know the changes in the pH of the water after liming the Minapadi land in the tidal swamp area, so that it is hoping that later it will be able to find out the pH value that is suitable and suitable for Minapadi activities, including the pH of the water that is suitable for the type of fish to use. This research was carried out from October to December 2020. The water samples collected directly on the land of Sungai Dua in Banyuasin Regency. Sampling water, pH during the study was carried out at several points on the rice field plots. The conclusion obtained during the observation of the pH value of the water before and after the observation of the pH value in the mina padi land of Sungai Dua Village which has been liming is that the pH value of the pH value increases and falls into the appropriate range for mina padi activities in Sungai Dua Village. Observing the pH value of water before and after observing the pH value in the Mina Padi land in Sungai Dua Village which has been limed, namely the pH value, the pH value increases and falls into the appropriate range for Mina Padi activities in Sungai Dua Village.